2013
DOI: 10.1111/j.1469-0691.2012.03957.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antibodies to phleboviruses within the sand fly fever Naples virus species in humans, northern Greece

Abstract: Phleboviruses are commonly detected in the Mediterranean region. In order to estimate the seroprevalence to Toscana virus (TOSV) and TOSV-like viruses in the human population in northern Greece, we tested serum samples from 595 apparently healthy individuals aged 1-87 years (median: 45 years) for the presence of TOSV IgG antibodies. A seroprevalence of 11.26% was observed, ranging from 0% to 23.5%. Seropositivity was significantly lower in children and adults <30 years of age. The high seroprevalence (>10%) ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
8
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
4
8
1
2
Order By: Relevance
“…At the outset of our study, the following data were available for Greece: (i) there was no serological data in domestic animals (cattle, goats, sheep, dogs or cats) for any phlebovirus transmitted by sand flies, (ii) in the 1970's, 13.1% of 38 adults living in Crete had NT-Abs against Naples virus, and 24.7% and 8.5% of 632 human sera from Athens inhabitants had NT-Abs against Naples virus and Sicilian virus, respectively [29]; (iii) more recent studies reported various rates of TOSV IgG using ELISA and/or IIF tests in continental Greece as well as in the Ionian and Aegean islands [810]; (iv) TOSV RNA (belonging to the lineage C) was detected in the CSF of a patient with meningitis [11], and (v) viral RNA corresponding to Adria virus, a novel virus belonging to the Salehabad species, was also identified in the CSF of a patient with meningitis [12, 13]. To date, SFSV or another SFS-like virus have been neither isolated nor detected by molecular techniques in Greece.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the outset of our study, the following data were available for Greece: (i) there was no serological data in domestic animals (cattle, goats, sheep, dogs or cats) for any phlebovirus transmitted by sand flies, (ii) in the 1970's, 13.1% of 38 adults living in Crete had NT-Abs against Naples virus, and 24.7% and 8.5% of 632 human sera from Athens inhabitants had NT-Abs against Naples virus and Sicilian virus, respectively [29]; (iii) more recent studies reported various rates of TOSV IgG using ELISA and/or IIF tests in continental Greece as well as in the Ionian and Aegean islands [810]; (iv) TOSV RNA (belonging to the lineage C) was detected in the CSF of a patient with meningitis [11], and (v) viral RNA corresponding to Adria virus, a novel virus belonging to the Salehabad species, was also identified in the CSF of a patient with meningitis [12, 13]. To date, SFSV or another SFS-like virus have been neither isolated nor detected by molecular techniques in Greece.…”
Section: Discussionmentioning
confidence: 99%
“…Sandfly fever has been described in Cyprus and Greece with both sporadic cases and epidemics [37]. In both countries, the high rates of antibodies observed in seroprevalence studies indicate that viruses belonging to Sandfly fever Naples and Sandfly fever Sicilian serocomplexes are transmitted by local sand flies to human populations [710]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies in the Greek population have shown that the prevalence of IgG antibodies against TOSV or antigenically related phlebovirus(es) is high (up to 50%), especially on the islands and coastal areas of the mainland [6,7,8]. A TOSV seroconversion was reported in 1993 in a German traveler returning from Greece [9].…”
Section: Introductionmentioning
confidence: 99%
“…Among these, TOSV is associated with neurotropism, a major cause of meningitis and encephalitis in the Mediterranean region ( 4 ). Recent studies in Greece showed that the seroprevalence of TOSV (and antigenically related viruses) ranges from 0% to 60%; the higher levels are found in the islands and the coastal regions ( 5 7 ). …”
mentioning
confidence: 99%